Late clotted haemothorax after blunt chest trauma. Issue 3 (May 1998) - Sinha, P; Sarkar, P
Abstract : A clotted haemothorax can develop any time after blunt chest trauma. Two cases are described in which late clotted haemothoraces developed which were treated by limited thoracotomy and evacuation of clots. Late clotted haemothorax may occur even in the absence of any abnormal initial clinical findings. Early detection and treatment is important to avoid the complications of fibrothorax and empyema with permanent pulmonary dysfunction. After blunt chest trauma patients should be advised to return to the accident and emergency department for assessment on development of any new chest symptom. Under these circumstances a chest x ray is mandatory to exclude a haemothorax.